Epidemiological trends in alcoholic cardiomyopathy burden: A 32-year global and Chinese analysis (1990–2021) with projections to 2036 - Fei Yan; Changfen Wang; Jiulin Chen; Zhaoxing Cao; Runze Huang; Zhangrong Chen (PLoS ONE, 2025)
Background: Alcoholic cardiomyopathy (ACM), a preventable yet overlooked cardiomyopathy subtype, disproportionately affects chronic alcohol users through alcohol-induced myocardial damage. Characterized by delayed clinical onset, ACM typically manifests as irreversible heart failure in middle age (45-69 years), creating missed opportunities for early intervention. Despite global cardiovascular mortality declines, ACM burden continues rising paradoxically in certain middle-high income countries like China, revealing gaps in current prevention strategies. This study systematically evaluates ACM’s global burden through prevalence, mortality and disability-adjusted life years (DALYs) metrics, using WHO-standardized methods to characterize spatiotemporal patterns across global, national, and subnational strata. Methods: We utilized the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 methodological framework to estimate the age-standardized rates (ASRs) of prevalenceand, mortality and DALYs for ACM. These estimates were stratified across key demographic dimensions including: Age groups (15-95+ years), Sex, Geographical regions (21 GBD-defined regions), the Socio-Demographic Index (SDI) quintiles, 204 countries and territories during the observation period 1990-2021. Furthermore, we employed Bayesian Age-Period-Cohort (BAPC) modeling with integrated nested Laplace approximations to project disease burden trajectories through 2036, incorporating uncertainty quantification via Markov chain Monte Carlo simulations. Results: Globally, ACM burden showed significant declines from 1990 to 2021, with age-standardized rates decreasing by 22.5-37.1% across prevalence, mortality and disability measures. However, China experienced a 200.4% case increase during this period, with rising mortality and disability rates contrary to global trends. The disease disproportionately affected males and middle-aged adults (45-69 years), with pronounced regional disparities in middle-high SDI areas. While population growth primarily drove disability-adjusted life year (DALY) increases, these regions also showed greatest potential for burden reduction through targeted interventions. Projections suggest continued global declines but only modest improvements in China through 2036. Conclusion: In 2021, ACM remained a significant global health burden, particularly affecting middle-aged and elderly populations with distinct demographic disparities. This study identified three critical issues: China’s unique epidemiological patterns, optimal intervention timing for high-risk populations, and sex-specific pathogenic mechanisms. Future research should prioritize developing precision prevention strategies for high-burden regions, including population-based alcohol control policies, early screening programs (especially for males aged 45-69), and personalized secondary prevention measures. Middle-high SDI regions warrant particular attention as priority intervention areas requiring cost-effectiveness implementation studies.